Kekuasaan Politik, Rivalitas Keagamaan, dan Xenofobia dalam Sejarah Kemartiran Kristen di Asia - Ebeneser Lumban Gaol (Dunamis: Jurnal Teologi dan Pendidikan Kristiani)
Abstract. Martyrdom plays a fundamental role in shaping the identity and faith journey of Christians in Asia. This study aimed to obtain understanding the factors that shape Christian martyrdom in Asia, especially the role of political power, religious rivalry, and xenophobia. Using a historical-comparative method, this study analyzed cases of persecution from the early Christian period to the modern era, such as in the Roman Empire, Persia, China, and Japan. The result of the study showed that martyrdom is a phenomenon that is closely related to social, political, and cultural dynamics. Thus, the results of this study can be a guide for more contextual evangelism efforts to minimize conflict and violence.